Remote functionalization of hydrocarbons with reversibility enhanced stereocontrol1. Issue 5 (20th May 2015) - Vasseur, Alexandre; Perrin, Lionel; Eisenstein, Odile; Marek, Ilan
<x xml:space="preserve">Abstract</x> Remote functionalization of hydrocarbons could be achieved through successive zirconocene-mediated allylic C–H bond activations followed by a selective C–C bond cleavage.